Egyptian National Postal Organization : Review of Asset Management Operations - World Bank (Washington, DC, 2013)
This report presents the missions observations and recommendations. The mission has not been able to review the investment manual and current investment procedures as the relevant documents have not been yet forwarded by Egyptian National Postal Organization (ENPO) as requested. ENPO was established in 1865 and since its creation it has always had a clear mandate of public service that remains dominant until today despite the growing competitive pressures that the organization is facing in most of its markets. ENPO's activities center around two major categories: postal and other services, and financial services. Postal services include letters (regular and express mails) and parcels. Other services are public services, such as bills payments (telecom, car insurance, and taxes) and government services, including pension payment and government money orders. ENPO currently holds 18 million savings accounts, against 8 million for the rest of the banking sector, making it the first financial institution in the country in terms of number of accounts. In terms of deposits however, ENPO remains under 10 percent which is typical for postal operators whose customers are usually low-income households with small savings, therefore the large number of accounts does not translate into a large amount of total savings. ENPO provides daily interest accounts, and postal savings passbook. More recently, it introduced the postal investment book with guaranteed principal.